(untitled) (Bangladesh Journal of Psychology, 2025)
The objective of this study was to investigate the relationship of anxiety, mental wellbeing, and socio-demographic influences in adolescents. Data were collected from 499 high school students (12-17 years, 34.3 % male and 65.7 % female) of four Bangla-medium schools in Dhaka city using the Bangla version of the Beck Anxiety Inventory for Youth (BAI-Y), the Mental Health Continuum-Short Form (MHC-SF), and a demographic questionnaire during regular school hours. Correlation analysis demonstrated that anxiety was negatively associated with overall mental health and its emotional and social dimensions. Independent sample t-tests revealed that male students and those from joint families exhibited better wellbeing but higher anxiety. Similar patterns were observed among students involved in extracurricular activities or bearing additional familial responsibilities. One-way ANOVA indicated significant differences across class levels, with Class 10 students showing notably lower anxiety and wellbeing than their junior peers. Students perceived socioeconomic status showed small yet meaningful differences in their social and overall wellbeing. Multiple regression analyses showed that socio-demographic factors accounted for 10.3% of the variance in anxiety—predicted by gender, participation in extracurricular activities, and additional family responsibilities—and 7.8% of the variance in mental wellbeing, predicted by gender, family structure, perceived socio-economic status, and participation in extracurricular activities. Results highlight the need for school-based mental health programs that consider variations in grade level, gender, and familial responsibilities, as these factors significantly influence adolescents’ anxiety and wellbeing, while considering the potential influence of additional factors on adolescent mental health. Bangladesh Journal of Psychology, Vol. 25, December 2025, pp. 30-49